Etiology-Specific Remodeling in Ventricular Tissue of Heart Failure Patients and Its Implications for Computational Modeling of Electrical Conduction - Sankarankutty, Aparna C.; Greiner, Joachim; Bragard, Jean; Visker, Joseph R.; Shankar, Thirupura S.; Kyriakopoulos, Christos P.; Drakos, Stavros G.; Sachse, Frank B. (Frontiers in Physiology, 2021)
With an estimated 64.3 million cases worldwide, heart failure (HF) imposes an enormous burden on healthcare systems. Sudden death from arrhythmia is the major cause of mortality in HF patients. Computational modeling of the failing heart provides insights into mechanisms of arrhythmogenesis, risk stratification of patients, and clinical treatment. However, the lack of a clinically informed approach to model cardiac tissues in HF hinders progress in developing patient-specific strategies. Here, we provide a microscopy-based foundation for modeling conduction in HF tissues. We acquired 2D images of left ventricular tissues from n=16 HF patients and n=5 donors. The composition and heterogeneity of fibrosis were quantified at a sub-micrometer resolution over an area of 1 mm2. From the images, we constructed computational bidomain models of tissue electrophysiology. We measured local upstroke velocities of the membrane voltage and anisotropic conduction velocities (CV). The fibrotic volume fraction was higher in HF than donors (39.68+/-14.23% vs. 22.09+/-2.72%, p<0.01), and lower in ischemic (IC) than nonischemic (NIC) cardiomyopathy (47.2+/-16.18% vs. 32.16+/-6.55%, p<0.05). The heterogeneity of fibrosis within each subject was highest for IC (27.1+/-6.03%) and lowest for donors (7.47+/-1.37%) with NIC (15.69+/-5.76%) in between. K-means clustering of this heterogeneity discriminated IC and NIC with an accuracy of 81.25%. The heterogeneity in CV increased from donors to NIC to IC. CV decreased with increasing fibrosis for longitudinal (R^2 = 0.28, p<0.05) and transverse conduction (R^2 = 0.46, p<0.01). The tilt angle of the CV vectors increased 2.1° for longitudinal and 0.91° for transverse conduction per 1% increase in fibrosis. Our study suggests that conduction fundamentally differs in the two etiologies due to the characteristics of fibrosis. Our study highlights the importance of the etiology-specific modeling of HF tissues and integration of medical history into electrophysiology models for personalized risk stratification and treatment planning.